High barrier bottle grade polyester and method for its preparation

By leveraging the synergistic effect of composite nano barrier agents and reactive compatibilizers, combined with a twin-screw extruder and vacuum exhaust design, the problems of poor gas barrier performance and acetaldehyde generation in PET bottle-grade polyester have been solved, achieving the preparation of bottle-grade polyester with high transparency, high barrier properties, and low acetaldehyde.

CN122628504APending Publication Date: 2026-08-25ANHUI HAOYUAN CHEM IND GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610745163.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing PET bottle-grade polyester has poor gas barrier properties. PEN is incompatible with PET, leading to interfacial permeation. High PEN content increases costs and reduces transparency. PET is prone to producing acetaldehyde during high-temperature melt processing, affecting food safety.

Method used

By employing composite nano-barrier agents and reactive compatibilizers, a physical maze effect is formed through modified nano-silica and halloysite nanotubes. Combined with styrene-glycidyl methacrylate copolymer compatibilizer, chemical bonds are formed, reducing PEN usage and improving interfacial bonding. A twin-screw extruder and vacuum exhaust design are used to reduce acetaldehyde generation.

Benefits of technology

Achieving high barrier performance with low PEN addition, maintaining good transparency, reducing oxygen permeability, and controlling acetaldehyde content at low levels, thereby reducing production energy consumption and raw material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to a kind of high barrier bottle grade polyester and its preparation method, belong to polyester technical field.The high barrier bottle grade polyester includes polyethylene terephthalate, polyethylene naphthalate, composite nano barrier agent, reactive compatibilizer.The composite nano barrier agent is composed of modified nano silicon dioxide and modified halloysite nanotube.The reactive compatibilizer is styrene-glycidyl methacrylate copolymer.The present application realizes the bottle grade polyester of high barrier, high transparency and low acetaldehyde under low PEN addition amount by the synergistic effect of the triple mechanism of intrinsic barrier of PEN, physical maze effect of composite nano barrier agent and interface strengthening of reactive compatibilizer, and the technology of master batch pre-dispersion process, vacuum exhaust and acetaldehyde absorption is combined, meets the requirement of food packaging, and is suitable for juice, tea beverage, edible oil and other packaging containers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyester technology, and more particularly to a high-barrier bottle-grade polyester and its preparation method. Background Technology

[0002] Polyethylene terephthalate (PET) boasts advantages such as high transparency, excellent mechanical properties, high food safety, and low cost, making it a primary material for manufacturing packaging containers for beverage bottles, edible oil bottles, and pharmaceutical packaging, widely used in the food, beverage, and daily chemical industries. However, ordinary PET has poor gas barrier properties, allowing gases such as oxygen and carbon dioxide to easily permeate through the PET packaging walls. For oxygen-sensitive products like fruit juices, tea beverages, and edible oils, gas permeation can lead to oxidation and spoilage of the contents, loss of aroma, and a decline in nutritional content, severely shortening shelf life. Therefore, significantly improving the gas barrier properties of PET while maintaining its good transparency and processability is a core technological bottleneck that urgently needs to be overcome in this field.

[0003] To improve the barrier properties of PET, existing technologies have mainly focused on the following improvement routes: multilayer lamination, surface coating, and blending modification. Multilayer lamination, such as PET / EVOH / PET, improves barrier performance by introducing a high-barrier interlayer between PET layers; however, it involves complex processes, high equipment investment, the risk of layer delamination, and makes the finished product difficult to recycle. Surface coating, such as silica coatings and amorphous carbon coatings, also achieves excellent barrier effects, but requires additional coating equipment and processes, and the coating is subject to wear and peeling. Blending modification involves directly melt-blending high-barrier polymers with PET; the process is relatively simple and easy to implement, making it one of the more favored industrial technologies.

[0004] In the blending modification route, polyethylene naphthalate (PEN) has significantly better intrinsic gas barrier properties than PET due to the rigid naphthalene ring structure in its molecular chain, and its chemical structure is similar to that of PET. It is considered an ideal blending component for improving the barrier properties of PET. However, the existing technology still has the following shortcomings when using PEN to modify PET: (1) PET and PEN are inherently incompatible. When blending, there are obvious gaps at the interface between the two phases, and gas molecules can easily penetrate from the interface, making it difficult to give full play to the barrier advantages of PEN; (2) In order to obtain a significant barrier improvement, a high proportion of PEN, such as 20-30 wt%, is often required, which leads to a significant increase in raw material costs; (3) The transparency of blends with high PEN content decreases, making it difficult to meet the transparency requirements of bottle-grade polyester; (4) PET is prone to generating acetaldehyde during high-temperature melt processing, which affects food safety. Summary of the Invention

[0005] To address the aforementioned problems in the prior art, this invention provides a high-barrier bottle-grade polyester and its preparation method, which can achieve high barrier properties, high transparency, and low acetaldehyde in bottle-grade polyester with low PEN addition.

[0006] The objective of this invention can be achieved through the following technical solutions: In a first aspect, a high-barrier bottle-grade polyester is provided, comprising the following raw materials in parts by weight: 100 parts of polyethylene terephthalate; 10-15 parts of polyethylene naphthalate; 0.7-2 parts of composite nano barrier agent; 0.3-1.0 parts of reactive compatibilizer.

[0007] Furthermore, the composite nano barrier agent is composed of modified nano silica and modified halloysite nanotubes, wherein the weight ratio of the modified nano silica to the modified halloysite nanotubes is 1:0.5-1:2.

[0008] Spherical SiO2 fills the gaps in tubular halloysite, extending the gas permeation path (labyrinth effect), and the combination of the two forms a "tube-sphere complementary" physical barrier network.

[0009] Furthermore, the modified nano-silica is nano-silica surface-treated with γ-glycidoxypropyltrimethoxysilane, with an average particle size of 20-60 nm; the modified halloysite nanotubes are halloysite nanotubes surface-treated with silane coupling agent, with an aspect ratio of 10-30.

[0010] Furthermore, the reactive compatibilizer is a styrene-glycidyl methacrylate copolymer with an epoxy equivalent of 500-700 g / eq, wherein the content of glycidyl methacrylate is 7-12 wt%.

[0011] Furthermore, the high-barrier bottle-grade polyester also contains 0.08-0.2 parts by weight of an antioxidant compound system and 0.02-0.05 parts by weight of an acetaldehyde absorbent; the antioxidant compound system is a mixture of antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) and antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite) in a weight ratio of 1:1 to 1:4; the acetaldehyde absorbent is one of o-aminobenzoamide or ethylene glycol aminobenzoate.

[0012] In a second aspect, a method for preparing the high-barrier bottle-grade polyester described in the first aspect is provided, comprising the following steps: (1) The composite nano barrier agent and polyethylene terephthalate are mixed in a weight ratio of 1:4-1:9 (i.e., the composite nano barrier agent accounts for 10-20 wt% of the total weight of the masterbatch), premixed and then melt-granulated to obtain the nano barrier masterbatch. (2) Mix the remaining polyethylene terephthalate (i.e., the remainder after deducting the portion used in step (1) from 100 parts of PET), polyethylene naphthalate, the nano barrier masterbatch obtained in step (1), the reactive compatibilizer, the antioxidant compound system, and the acetaldehyde absorbent evenly. (3) The mixture from step (2) is melt-blended, extruded, and granulated in a twin-screw extruder to obtain the base polyester; (4) The base polyester obtained in step (3) is reacted in a solid-phase polycondensation apparatus at 210-235°C and under vacuum for 4-12 hours to obtain high-barrier bottle-grade polyester.

[0013] Furthermore, in step (3), the twin-screw extruder is provided with at least two meshing zones and a set of reverse thread elements, and the twin-screw extruder is provided with at least two vacuum exhaust ports.

[0014] Furthermore, the two vacuum exhaust ports are arranged as follows: the first vacuum exhaust port is located in the middle of the melting section, and the second vacuum exhaust port is located between the end of the melting section and the homogenization section. The vacuum degree of each vacuum exhaust port is -0.08MPa to -0.098MPa.

[0015] Furthermore, in step (3), the length-to-diameter ratio of the twin-screw extruder is 44:1-52:1, and the melting section temperature is 260-275℃.

[0016] Furthermore, in step (4), the intrinsic viscosity of the obtained high-barrier bottle-grade polyester is 0.72-0.84 dL / g.

[0017] The beneficial effects of this invention are as follows: (1) This invention uses styrene-glycidyl methacrylate copolymer as a reactive compatibilizer. During melt blending, the epoxy groups on its molecular chain undergo ring-opening reactions with the carboxyl groups at the ends of the PET and PEN molecular chains, forming covalent bonds and improving the interfacial bonding between the inherently incompatible PET and PEN. At the same time, after surface treatment with an epoxy silane coupling agent, the surface of the composite nano barrier agent also has epoxy groups, which can also react with the terminal carboxyl groups of PET and PEN, allowing the nanoparticles to be chemically anchored in the polymer matrix. Through the synergistic chemical bonding of the reactive compatibilizer and the modified composite nano barrier agent, PEN is distributed in the continuous PET phase as a fine and uniform dispersed phase. The interfacial defects between the two phases are significantly reduced, and gas molecules cannot quickly permeate from the interface, thus fully leveraging the intrinsic barrier advantage of PEN.

[0018] (2) This invention achieves an oxygen permeability of 35-40 cm⁻¹ for bottle-grade polyester through the synergistic effect of the intrinsic barrier properties of PEN, the physical maze effect of the composite nano barrier agent, and the interfacial reinforcement of the reactive compatibilizer, with a PEN addition amount of only 10-15 parts. 3 / m 2 The use of ·d·bar reduces PEN consumption, saving on raw material costs.

[0019] (3) This invention strictly controls the amount of PEN added to 10-15 parts to avoid a sharp increase in haze due to the difference in refractive index caused by high PEN content; the average particle size of the nano silica in the composite nano barrier agent is 20-60 nm, which is smaller than the wavelength of visible light and is not prone to significant light scattering; the masterbatch pre-dispersion process effectively prevents secondary agglomeration of nanoparticles and avoids the increase in haze caused by agglomerates; the reactive compatibilizer refines the size of the PEN dispersed phase to the submicron level, further reducing light scattering at the phase interface. Through the combined effect of the above multiple means, the haze of the product of this invention is controlled at 4.2%-4.8%, maintaining good transparency while achieving high barrier properties.

[0020] (4) This invention employs a multi-stage high-vacuum exhaust design for a twin-screw extruder: the first vacuum exhaust port is located in the middle of the melting section to remove moisture and low-boiling-point substances, reducing acetaldehyde generated by hydrolysis degradation at the source; the second vacuum exhaust port is located between the end of the melting section and the homogenization section to physically remove the generated small-molecule acetaldehyde. Simultaneously, the acetaldehyde absorbent added to the formulation can chemically react with acetaldehyde, fixing it chemically. Through the dual effects of physical removal and chemical capture, this invention controls the acetaldehyde content at a low level before solid-phase polycondensation, reducing the acetaldehyde content of the final product to 0.7-0.9 μg / g. Furthermore, because the first two acetaldehyde control measures effectively reduce the initial acetaldehyde value, the subsequent solid-phase polycondensation time can be shortened to 4-12 hours, reducing production energy consumption. Detailed Implementation

[0021] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.

[0022] Preparation of modified nano silica: Nano silica was added to an ethanol / water mixed solvent, γ-glycidoxypropyltrimethoxysilane (KH-560) was added, the pH was adjusted to 4-5, and the reaction was stirred at 75℃ for 4 hours. After centrifugation, washing and drying, KH-560 modified nano silica was obtained.

[0023] Preparation of modified halloysite nanotubes: Halloysite nanotubes were added to an ethanol / water mixed solvent, γ-aminopropyltriethoxysilane (KH-550) was added, the pH was adjusted to 4-5, and the reaction was stirred at 75℃ for 4 hours. After centrifugation, washing and drying, KH-550 modified halloysite nanotubes were obtained.

[0024] Example 1 In this embodiment, the amounts of each component are as follows: Polyethylene terephthalate (PET): 100 parts Polyethylene naphthalate (PEN): 12.5 parts Composite nano barrier agent: 1.35 parts (including 0.675 parts modified nano silica and 0.675 parts modified halloysite nanotubes) Reactive compatibilizer: 0.65 parts Antioxidant compound system: 0.14 parts (antioxidant 1010 and antioxidant 168 weight ratio 1:2) Acetaldehyde absorbent: 0.035 parts (1) Preparation of nano barrier masterbatch 1.35 parts of composite nano barrier agent were mixed with polyethylene terephthalate at a weight ratio of 1:6.5 (i.e., the composite nano barrier agent accounted for 13.3 wt% of the total weight of the masterbatch), premixed, and then melt-granulated to obtain nano barrier masterbatch.

[0025] (2) Mixing raw materials Mix the remaining polyethylene terephthalate (i.e., the remainder after deducting the portion used in step (1) from 100 parts), 12.5 parts of polyethylene naphthalate, the nano barrier masterbatch obtained in step (1), 0.65 parts of reactive compatibilizer, 0.14 parts of antioxidant compound system, and 0.035 parts of acetaldehyde absorbent evenly.

[0026] (3) Melt blending granulation The mixture from step (2) was melt-blended, extruded, and granulated in a twin-screw extruder. The twin-screw extruder had an aspect ratio of 48:1, a melt zone temperature of 268°C, a screw speed of 240 rpm, and a residence time of 140 seconds. The twin-screw extruder had two meshing zones and a set of reverse screw elements, and two vacuum exhaust ports. The first vacuum exhaust port was located in the middle of the melt zone, and the second vacuum exhaust port was located between the end of the melt zone and the homogenization zone. The vacuum degree of each vacuum exhaust port was -0.09 MPa. The base polyester was obtained.

[0027] (4) Solid-phase condensation and viscosity enhancement The base polyester obtained in step (3) was reacted in a solid-state polycondensation apparatus at 222°C under vacuum for 8 hours to obtain a high-barrier bottle-grade polyester. Its intrinsic viscosity was measured to be 0.78 dL / g.

[0028] Example 2 In this embodiment, the amounts of each component are as follows: Polyethylene terephthalate (PET): 100 parts Polyethylene naphthalate (PEN): 10 parts Composite nano barrier agent: 0.7 parts (including 0.35 parts modified nano silica and 0.35 parts modified halloysite nanotubes) Reactive compatibilizer: 0.3 parts Antioxidant compound system: 0.08 parts (antioxidant 1010 and antioxidant 168 in a 1:1 weight ratio) Acetaldehyde absorbent: 0.02 parts (1) Preparation of nano barrier masterbatch 0.7 parts of the composite nano barrier agent were mixed with polyethylene terephthalate at a weight ratio of 1:4 (i.e., the composite nano barrier agent accounted for 20 wt% of the total weight of the masterbatch), and then melt-granulated to obtain the nano barrier masterbatch.

[0029] (2) Mixing raw materials Mix the remaining polyethylene terephthalate (i.e., the remainder after deducting the portion used in step (1) from 100 parts), 10 parts of polyethylene naphthalate, the nano barrier masterbatch obtained in step (1), 0.3 parts of reactive compatibilizer, 0.08 parts of antioxidant compound system, and 0.02 parts of acetaldehyde absorbent evenly.

[0030] (3) Melt blending granulation The mixture from step (2) was melt-blended, extruded, and granulated in a twin-screw extruder. The twin-screw extruder had an aspect ratio of 44:1, a melt zone temperature of 260°C, a screw speed of 200 rpm, and a residence time of 120 seconds. The twin-screw extruder had two meshing zones and a set of reverse screw elements, and two vacuum exhaust ports. The first vacuum exhaust port was located in the middle of the melt zone, and the second vacuum exhaust port was located between the end of the melt zone and the homogenization zone. The vacuum degree of each vacuum exhaust port was -0.08 MPa. The base polyester was obtained.

[0031] (4) Solid-phase condensation and viscosity enhancement The base polyester obtained in step (3) was reacted in a solid-state polycondensation apparatus at 210°C under vacuum for 12 hours to obtain a high-barrier bottle-grade polyester. Its intrinsic viscosity was measured to be 0.72 dL / g.

[0032] Example 3 In this embodiment, the amounts of each component are as follows: Polyethylene terephthalate (PET): 100 parts Polyethylene naphthalate (PEN): 15 parts Composite nano barrier agent: 2.0 parts (including 1.0 part of modified nano silica and 1.0 part of modified halloysite nanotubes) Reactive compatibilizer: 1.0 part Antioxidant compound system: 0.2 parts (antioxidant 1010 and antioxidant 168 in a weight ratio of 1:4) Acetaldehyde absorbent: 0.05 parts (1) Preparation of nano barrier masterbatch 2.0 parts of composite nano barrier agent were mixed with polyethylene terephthalate at a weight ratio of 1:9 (i.e., the composite nano barrier agent accounted for 10 wt% of the total weight of the masterbatch), premixed, and then melt-granulated to obtain nano barrier masterbatch.

[0033] (2) Mixing raw materials Mix the remaining polyethylene terephthalate (i.e., the remainder after deducting the portion used in step (1) from 100 parts), 15 parts of polyethylene naphthalate, the nano barrier masterbatch obtained in step (1), 1.0 part of reactive compatibilizer, 0.2 parts of antioxidant compound system, and 0.05 parts of acetaldehyde absorbent evenly.

[0034] (3) Melt blending granulation The mixture from step (2) was melt-blended, extruded, and granulated in a twin-screw extruder. The twin-screw extruder had an aspect ratio of 52:1, a melt zone temperature of 275°C, a screw speed of 280 rpm, and a residence time of 160 seconds. The twin-screw extruder had two meshing zones and a set of reverse screw elements, and two vacuum exhaust ports. The first vacuum exhaust port was located in the middle of the melt zone, and the second vacuum exhaust port was located between the end of the melt zone and the homogenization zone. The vacuum degree of each vacuum exhaust port was -0.098 MPa. The base polyester was obtained.

[0035] (4) Solid-phase condensation and viscosity enhancement The base polyester obtained in step (3) was reacted in a solid-state polycondensation apparatus at 235°C under vacuum for 4 hours to obtain a high-barrier bottle-grade polyester. Its intrinsic viscosity was measured to be 0.84 dL / g.

[0036] Comparative Example 1 Ordinary PET Comparative Example 2 Based on Example 1, without adding composite nano barrier agents and reactive compatibilizers, all other conditions are the same as in Example 1.

[0037] Comparative Example 3 Based on Example 1, without adding composite nano barrier agent, other conditions are the same as in Example 1.

[0038] Comparative Example 4 Based on Example 1, the composite nanobarrier was replaced with a composite nanobarrier of unmodified nano-silica and halloysite nanotubes, while other conditions remained the same as in Example 1.

[0039] Comparative Example 5 Based on Example 1, the composite nano barrier agent was replaced with a single modified nano silica, and other conditions were the same as in Example 1.

[0040] Comparative Example 6 Based on Example 1, the composite nanobarrier was replaced with a single modified halloysite nanotube, and other conditions were the same as in Example 1.

[0041] Comparative Example 7 Based on Example 1, no reactive compatibilizer was added, and other conditions were the same as in Example 1.

[0042] Comparative Example 8 Based on Example 1, the twin-screw extruder used in the preparation method is not under vacuum and there is no acetaldehyde absorbent, while other conditions are the same as in Example 1.

[0043] Comparative Example 9 Based on Example 1, the PEN content was replaced with 20 parts, and other conditions were the same as in Example 1.

[0044] Comparative Example 10 Based on Example 1, the preparation method does not involve pre-dispersion of masterbatch, but is a normal blending, and other conditions are the same as in Example 1.

[0045] Performance testing Bottle-grade polyester obtained in Examples 1-3 and Comparative Examples 1-10 was molded into sheets.

[0046] Oxygen transmission rate: Referring to GB / T 19789-2021 standard, the coulometric method is adopted. The sheet is fixed in the test chamber, oxygen is introduced on one side and nitrogen is introduced on the other side. After the oxygen passes through the sheet, it is carried by the nitrogen to the sensor for detection.

[0047] Haze: Referring to GB / T 2410-2008 standard, the haze meter method is used. After parallel light passes through the sheet, the total transmitted light and scattered light flux are measured by integrating sphere. Acetaldehyde content: Refer to SH / T 1817-2017 standard, headspace gas chromatography, the sample is heated in the headspace vial, acetaldehyde is released into the gas phase, and the sample is injected for analysis.

[0048] Table 1. Performance test results for each embodiment and comparative example.

[0049] The test results show that Examples 1-3 all exhibited excellent barrier and transparency properties, and low acetaldehyde content. Compared with the examples, Comparative Example 1, using ordinary PET, had a higher oxygen permeability but insufficient barrier properties. Comparative Example 2, a simple blend of PET and PEN without composite nano-barrier agents or reactive compatibilizers, had both high oxygen permeability and haze. Comparative Example 3, without composite nano-barrier agents, had slightly lower oxygen permeability and haze than Comparative Example 2. Comparative Example 4 used unmodified nano-silica and halloysite nanotubes, Comparative Example 5 used only modified nano-silica, and Comparative Example 6 used only modified halloysite nanotubes; both had higher oxygen permeability and haze than the examples. Comparative Example 7, without reactive compatibilizers, had significantly higher oxygen permeability and haze than the examples. Comparative Example 8, without vacuum exhaust and without acetaldehyde absorbents, had an acetaldehyde content of 2.1 μg / g, significantly higher than the examples. Comparative Example 9, using a high PEN addition, had a slightly better oxygen permeability than the Example, but its haze was significantly higher, increasing raw material costs. Comparative Example 10, without masterbatch pre-dispersion, had significantly higher haze than the Example.

[0050] In summary, this invention achieves high barrier properties, high transparency, and low acetaldehyde in bottle-grade polyester with low PEN content through the synergistic effect of PEN, modified composite nano barrier agent, and reactive compatibilizer, combined with masterbatch pre-dispersion process and vacuum degassing and acetaldehyde absorption technology.

[0051] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A high-barrier bottle-grade polyester, characterized in that, It contains the following ingredients by weight: 100 parts of polyethylene terephthalate; 10-15 parts of polyethylene naphthalate; 0.7-2 parts of composite nano barrier agent; 0.3-1.0 parts of reactive compatibilizer.

2. The high-barrier bottle-grade polyester according to claim 1, characterized in that, The composite nanobarrier is composed of modified nano-silica and modified halloysite nanotubes, with the weight ratio of modified nano-silica to modified halloysite nanotubes being 1:0.5-1:

2.

3. The high-barrier bottle-grade polyester according to claim 1, characterized in that, The modified nano-silica is nano-silica surface-treated with γ-glycidyl etheroxypropyltrimethoxysilane, with an average particle size of 20-60 nm; the modified halloysite nanotubes are halloysite nanotubes surface-treated with silane coupling agent, with an aspect ratio of 10-30.

4. The high-barrier bottle-grade polyester according to claim 1, characterized in that, The reactive compatibilizer is a styrene-glycidyl methacrylate copolymer with an epoxy equivalent of 500-700 g / eq and a glycidyl methacrylate content of 7-12 wt%.

5. The high-barrier bottle-grade polyester according to claim 1, characterized in that, The high-barrier bottle-grade polyester also contains 0.08-0.2 parts by weight of an antioxidant compound system and 0.02-0.05 parts by weight of an acetaldehyde absorbent; the antioxidant compound system is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1-1:4; the acetaldehyde absorbent is one of o-aminobenzoamide or ethylene glycol aminobenzoate.

6. A method for preparing high-barrier bottle-grade polyester as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) The composite nano barrier agent and polyethylene terephthalate are mixed in a weight ratio of 1:4-1:9, premixed and then melt-granulated to obtain nano barrier masterbatch. (2) Mix the remaining polyethylene terephthalate, polyethylene naphthalate, the nano barrier masterbatch obtained in step (1), the reactive compatibilizer, the antioxidant compound system, and the acetaldehyde absorbent evenly. (3) The mixture from step (2) is melt-blended, extruded, and granulated in a twin-screw extruder to obtain the base polyester; (4) The base polyester obtained in step (3) is reacted in a solid-phase polycondensation apparatus at 210-235°C and under vacuum for 4-12 hours to obtain high-barrier bottle-grade polyester.

7. The method for preparing high-barrier bottle-grade polyester according to claim 6, characterized in that, In step (3), the twin-screw extruder is provided with at least two meshing zones and a set of reverse thread elements, and the twin-screw extruder is provided with at least two vacuum exhaust ports.

8. The method for preparing high-barrier bottle-grade polyester according to claim 7, characterized in that, The two vacuum exhaust ports are located as follows: the first vacuum exhaust port is located in the middle of the melting section, and the second vacuum exhaust port is located between the end of the melting section and the homogenization section. The vacuum degree of each vacuum exhaust port is between -0.08MPa and -0.098MPa.

9. The method for preparing high-barrier bottle-grade polyester according to claim 6, characterized in that, In step (3), the length-to-diameter ratio of the twin-screw extruder is 44:1-52:1, and the melting zone temperature is 260-275℃.

10. The method for preparing high-barrier bottle-grade polyester according to claim 6, characterized in that, In step (4), the intrinsic viscosity of the obtained high-barrier bottle-grade polyester is 0.72-0.84 dL / g.